Paranormal sightings after general anaesthesia / Farah Nur Tedin Ng, Nur Sabrina Md Ali and Sabrina Peter - Tedin Ng, Farah Nur; Md Ali, Nur Sabrina; Peter, Sabrina (Faculty of Dentistry, 2025)
Hypnagogic hallucinations are visual, auditory, tactile, or other sensory events that are not actually present, experienced during hypnagogia, a period of transition from wakefulness to sleep. These hallucinations were reported to be brief and mostly visual in nature. We hereby report a rare incidence of this phenomenon occurring in a 61-year-old woman presented with impending Ludwig’s angina at our centre. She began experiencing hypnogogic hallucinations when she started to doze off at night after an incision and drainage procedure was carried out under general anaesthesia earlier that day. Upon closing her eyes, she had a clear view of people moving around performing chores. The events were so vivid that she was convinced they were of paranormal origin, which subsequently led to sleep deprivation. These hallucinations immediately disappeared simply by opening her eyes. She eventually sought psychiatric treatment, and the symptoms gradually decreased with full remission on postoperative day 5. Her daily appetite and behaviour were normal throughout her hospital stay. Although postoperative sleep disturbances are often described, hypnagogic hallucinations postgeneral anaesthesia were documented in only three cases to date following cardiovascular and orthopaedic surgery. To date, the aetiopathophysiology of this type of visual hallucination remains to be unravelled.